Development of Android-Based IPMLM with Scaffolding Learning Approach in Newton’s Law of Motion Material to Increase HOTS - Ardiyati, Tiara Kusuma; Suparno, Suparno; Eveline, Erlin; Dasilva, Beatrix Elvi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Combination of Android-based IPMLM and scaffolding acts as a synergism that increase students' actual abilities towards their potential abilities (ZPD). Thus, it can bridge students to achieve HOTS. This study aimed to: a) produce an Android-based IPMLM with scaffolding learning approach in Newton's law of motion material that is feasible to apply to increase high school students’ HOTS; b) examine the effectiveness of android-based IPMLM with scaffolding learning approach in Newton's law of motion material in increasing high school students’ HOTS. This R&D used the 4-D model consisted of defining, designing, developing, and disseminating stages. Empirical test subjects of HOTS items were students of class XI MIPA, subjects of IPMLM readability test and extensive trial were students of class X MIPA. The extensive trial took two classes in each school, namely experimental and control class. Data collected through questionnaires and tests. Data analysis techniques included calculation of average scores, Aiken's validity index, item fit MNSQ INFIT-OUTFIT parameters, item reliability, and Anova mixed design test. The results showed that: 1) the developed Android-based IPMLM is feasible to be used in learning with scaffolding approach in Newton's law of motion material to increase high school students’ HOTS; 2) The increase of HOTS in the experimental class is greater than the control class. Hence, an Android-based IPMLM with scaffolding learning approach is effective to increase high school students’ HOTS, especially in Newton's law of motion material.